(untitled) (Journal of Private and Commercial Law, 2025)
A court summons via registered letter has different implementation procedures from a manual court summons by handing over a letter by a postal officer which was previously handed over by a bailiff, This research aims to determine the level of legal effectiveness of summons by registered letter and how to overcome the obstacles that arise in implementing summons by registered letter at the Ambarawa Religious Court. This research is qualitative research with an empirical legal research approach. The implementation of the recorded summons has not been effective in terms of legal factors and facilities and infrastructure factors. The Supreme Court needs to improve regulations and provide adequate facilities and infrastructure and needs to carry out monitoring and evaluation of PT Pos Indonesia (Persero) which is then carried out by the court and each postal branch.